assume that no variable equals 0

## Simplify. a2xa6

Tutors, please sign in to answer this question.

# 2 Answers

If the problem says a^{2} x
a^{6}, then that is the same thing as having 2 a's being multiplied by each other, and then being multiplied by 6 a's, so

(a • a)(a • a • a • a • a • a) = a^{8}.

In general when you are multiplying two numbers that have the same base, you can keep the base and add their exponents.

So a^{2} • a^{6} = a^{2+6} = a^{8}.

2a multiplied by 6a = 2*6*a*a=12a^2